Residential Mobility, Migration and Economic Incentives - the Case of Hungary in 1990-1999 - Zsombor Cseres-Gergely (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2002)
Mobility in Hungary is a relatively infrequent phenomenon of which we have mostly aggregate-level information. I use settlement- and individual level data to show a more elaborate picture of the Hungarian population moving house across settlements and regions between 1990 and 1999. Along with giving an aggregate overview of mobility in the decade, characteristics of the mobile population is described. Using a simple economic model, I estimate the probabilities of moving house both from aggregate and individual data, and look at its response to economic incentives given by geographic differences in wages and unemployment. The findings show two main results. Firstly, the flow of people does follow wage and unemployment differences as expected, although exact parameter estimates vary in different models. Secondly, the findings show considerable heterogeneity on the individual level that prompts caution in extending results from simple local models to large distance or cross-border migration. Clear signs of the dominant change in mobility, a strong suburban development, is apparent that goes right against local labour market benefits.
Keywords: 330